(untitled) (Research, Society and Development, 2021)
Objective: to build and validate an e-book on patient care in the home environment. Methodology: study of the methodological type of content validation with expert judges, carried out from August 2020 to January 2021, in the municipality of Manaus, Amazonas, Brazil. A questionnaire was applied that uses the Likert scale. The instrument assesses 5 blocks: general impression, objective, content, relevance and language. The validation took place via Google Forms. Ten expert judges participated. Quantitative analysis was performed using Excel software to calculate Content Validity Index. The value of 80% was stipulated as acceptable for validation. Results: the study obtained as a final result the construction and validation of the e-book “Manual for home care”. The product was considered satisfactory, with a global Content Validity Index among the judges of 0.94 (94%). The judges suggested improvements in terms of technical terms, which were considered and modified for the final version, which will be made available for inclusion in the Best at Home in Manaus Program. Conclusion: the e-book was validated in terms of content, visual and relevance by the judges, obtaining satisfactory rates above the stipulated value. Therefore, it is an educational technology that can be used by caregivers and patients in the context of the Best at Home program, to promote more effective care.